A web-based system grab tutor management system with SMS notification / Zatil Syamimi Mohd Zamri - Mohd Zamri, Zatil Syamimi (2020)
The aim of this study is to address the inherent issue in finding suitable tutor match among the students and teachers. The idea is to design and develop a web-based system for Grab Tutor Management System with SMS Notifications. The common problems encountered by any students are the difficulties in finding the suitable tutors based on their preferred choice. The current existing web application are still lack of responsive elements where they just only provide the fill-in form to search for the tutors. This project is focused on designing a web development for finding private tutors for Sigma One Tuition Centre in Kelantan, Malaysia. The system is targeted to secondary school, which is focused on SPM candidates. The target users for the system are tutor and student. To ensure the effectiveness of this system, this system is integrated with the SMS Notifications that can inform the users before the class session. The System Development Life Cycle (SDLC) Waterfall Model was adapted as its development methodology. This web-based system has been developed using PHP and HTML and SQL for database. In order to evaluate the application, it goes through a series of testing which are the functional testing and User Acceptance Testing. The User Acceptance Testing (UAT) was conducted with 30 participants using a Google Form platform that consists of student and teachers from any secondary school background in respected area. The results indicate positive acceptance where 98% users are strongly agreed that this system is easy to use. Therefore, the study has successfully developed a web-based Grab Tutor Management System with SMS Notifications.